EVALUATION OF HEALTH RISK ASSESSMENT FOR CADMIUM, LEAD AND ZINK IN SOME COMMON CANNED FOODS IN ERBIL CITY MARKETS - Shahla Sherwan Rasool; Dalshad Aziz Darwesh (Zanco Journal of Pure and Applied Sciences, 2022)
This study was conducted for assess health hazard and concentration of some heavy metals including, Zinc (Zn), Cadmium (Cd), and Lead (Pb) in some canned foods involved canned fish, canned cheese and canned tomato paste that selected randomly from various markets in Erbil city. The design was completely randomized (CRD) with three replications. The metals content were determined by atomic absorption, in mg/kg, wet weight. However, the non-carcinogenic health risk of determined heavy metals is assessed using the target hazard quotient (THQ) and hazard index (HI). The outcomes showed that Zn has the highest level among heavy metals in all canned foods, While for Pb and Cd content in all samples were within acceptable range guideline that reported by WHO-FAO. According to the values of HQ and HI heavy metal in canned food, pose no health concern with HI < 1. Given the increased demands for canned foods as a result of changing lifestyles, continuous monitoring of canned products is essential. Keywords: food contamination, heavy metals, health risk assessment, canned foods